The Environment and Journalists Challenges on Reporting Financial Corruption in Sudan - Bashir Hamid, Yassin (International Journal of Psychosocial Rehabilitation, 2020)
Media could have an effective role in curbing corruption when there is access to information, freedom of expression, and a professional and ethical code of investigative journalism; hence, the present study aims to identify the challenges facing journalists in reporting financial corruption in Sudan. The present study adopted a qualitative research method using in-depth interviews to adequately probe the perceptions of the Sudanese journalists and editors to explore how the challenges facing journalists, such as censorship restrictive laws, economic pressures, and press freedom, affected the Sudanese newspapers’ framing of the issues of corruption in Sudan. A purposeful sampling method was adopted in selecting 20 Sudanese journalists across both governmental and private newspapers operating in Sudan. In order to achieve clearer understandings of the journalists’ perspectives, the study adequately supported a theme generated by means of employing NVivo 8 software. The findings revealed that the working environment influences corruption with its secondary themes, such as transportation and facilities, security threats, economic pressures, and political pressures. Additionally, the findings also generated themes and their five sub-themes, which were later analyzed in detail.